ENHANCING ARABIC LANGUAGE COMPETENCE THROUGH THE HELLOTALK APPLICATION: TA‘ZĪZ AL-KAFĀ’AH AL-LUGHAWIYYAH AL-‘ARABIYYAH MIN KHILĀL TAṬBĪQ HELLOTALK - Yulia Rusiadi; Ade Ritonga (Muaddib: Journal of Arabic Language and Literature, 2025)
The background of this research departs from the need for learning media that can be an intermediary for direct communication between students and native Arabic speakers. In the modern era of digital education, mobile applications have become essential tools for language acquisition. One such application, HelloTalk, offers interactive features that allow learners to engage in real-time conversations with native speakers. This study aims to examine how the application contributes to the development of Arabic speaking skills—particularly in terms of vocabulary (mufradat), grammar (qawaid), and oral expression (maharah al-kalam). Furthermore, it seeks to explore the benefits and limitations of HelloTalk as perceived by its users, providing insights into both the opportunities and challenges faced in the process of learning Arabic through digital platformsThe research method used is descriptive qualitative approach. Data were obtained through interviews, observations, and documentation. The results show that Hello Talk contributes positively to vocabulary improvement, vocabulary accuracy, and speaking fluency. Features such as voice note, room chat, hello Arabic, auto-correction, and other supporting features, and interaction with native speakers encourage more contextual and meaningful learning. However, this study also found obstacles such as limited internet access, lack of response from native speakers, not focusing on learning, and privacy concerns.